2019
DOI: 10.1111/ecno.12129
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal sustainability of current account imbalances: New evidence from the OECD countries

Abstract: This study estimates the intertemporal model for the relationship between exports and imports and examines the sustainability of current account deficits (CADs) and the validity of intertemporal budget constraint for 24 Organisation for Economic Co‐operation and Development countries. The standard ordinary least squares (OLS)‐based two‐step Engle and Granger test, the cointegration regression Durbin–Watson (CRDW) test, and the Stock–Watson test performed on the one‐regime model with time‐invariant parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 113 publications
2
4
0
1
Order By: Relevance
“…Our first sub-sample covers the period 1970-1999 to allow for sufficient time series observations. We found that the studies by Singh (2015Singh ( , 2019 are similar to ours in this regard. Singh (2015Singh ( , 2019 conducted similar sub-sample analyses and tested for what he referred to as "a break down in cointegration between exports and imports" for the case of India and the OECD nations, respectively.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our first sub-sample covers the period 1970-1999 to allow for sufficient time series observations. We found that the studies by Singh (2015Singh ( , 2019 are similar to ours in this regard. Singh (2015Singh ( , 2019 conducted similar sub-sample analyses and tested for what he referred to as "a break down in cointegration between exports and imports" for the case of India and the OECD nations, respectively.…”
Section: Introductionsupporting
confidence: 88%
“…We found that the studies by Singh (2015Singh ( , 2019 are similar to ours in this regard. Singh (2015Singh ( , 2019 conducted similar sub-sample analyses and tested for what he referred to as "a break down in cointegration between exports and imports" for the case of India and the OECD nations, respectively. His results show that there is a breakdown of the cointegration relationship over some periods.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations